Governing animals : animal welfare and the liberal state - Smith, Kimberly K., 1966- (New York ; Oxford : Oxford University Press, 2012)
'Governing Animals' explores the role of the liberal state in protecting animal welfare. Examining liberal concepts such as the social contract and representation, Smith argues that liberalism properly understood can recognize the moral status and social meaning of animals and provides guidance in fashioning animal policy.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 16, 2012).
Keywords: Animal welfare -- Government policy; Animal rights -- Government policy; Liberalism -- Social aspects